D.O. Sag Equation Calculations - Bengtson, Harlan (McGraw-Hill's AccessEngineering., 2020)
This Excel workbook has four worksheets for making dissolved oxygen sag calculations using the Streeter-Phelps and related equations. One of the worksheets is used to calculate values for the reaertion rate constant and for the deoxygenation rate constant at the temperature of the receiving stream after mixing with the waste stream. A second worksheet calculates the critical (minimum) D.O. concentration and the downstream distance to that minimum D.O. concentration. A third worksheet calculates the D.O. at a user-specified downstream distance to that minimum D.O. concentration. A fourth worksheet prepares a plot of the D.O. Sag Curve. The Streeter-Phelps equation is used in this Excel workbook.